PENGARUH WORK-FAMILY CONFLICT TERHADAP KINERJA KARYAWAN MELALUI SELF- EFFICACY SEBAGAI VARIABEL MEDIASI - Shofi Fadhila (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
This study aims to measure and analyze the effect of work-family conflict on employee performance through self-efficacy as a mediating variable for bank X employees in the Kediri region. This research is a causal research with a quantitative approach, with a population of 67 banking employees, and the sampling technique used in this research is saturated sample. Data analysis in this study was analyzed using the partial least squares structural equation model (SEM-PLS) with the help of SmartPLS 4.0.9 software. The results of the study show that work- family conflict has a significant negative effect on employee performance, work-family conflict has a significant negative effect on self-efficacy, self-efficacy has a significant positive effect on employee performance, and self-efficacy is proven to mediate the relationship between work- family conflict on employee performance. Companies must pay more attention to their employees, because a high level of work-family conflict will have a negative effect on their performance, high work-family conflict will also reduce the self-efficacy of employees, but this can be overcome with the help of self- efficacy which can mediate the relationship between work-family conflict and employee performanc